188k views
4 votes
Which of the following is the solution of the system of equations below? 6x+6y=-6 5x+y=-13

1 Answer

2 votes

First, we divide the first equation by -6


\begin{gathered} 6x+6y=-6 \\ -x-y=1 \end{gathered}

Then, we combine this equation with the second one


\begin{gathered} 5x-x+y-y=1-13 \\ 4x=-12 \\ x=-(12)/(4) \\ x=-3 \end{gathered}

Now, we use the x-value to find y


\begin{gathered} 5x+y=-13 \\ 5(-3)+y=-13 \\ -15+y=-13 \\ y=-13+15 \\ y=2 \end{gathered}

Hence, the solution to the system is (-3, 2).

User Yusef
by
5.4k points